Analysis of Weld Defects and Their Solutions in Manual Welding of Carbon Steel - Albaru, Agung; Syaputra, Muhammad Lyan; Balqis, Dinda; Afriandi, Irvan; Hasibuan, Fardin (Universitas Riau Kepulauan, 2025)
Welding is one of the most commonly used metal joining processes in the manufacturing and construction industries. However, this process often results in defects in the weld joint, especially in manual welding of carbon steel, which can affect the quality and strength of the joint. This study aims to analyze the types of welding defects that occur in manual welding of carbon steel, identify their main causes, and provide technical solutions to minimize such defects. The methods used include visual inspection, penetrant testing (PT), and macrostructure examination of the welded joints. The results show that the most common defects found are porosity, undercut, incomplete fusion, and slag inclusion. The primary causes of these defects include improper welding parameter settings, inadequate cleanliness of the metal surface, and the skill level of the operator. As solutions, it is recommended to conduct regular operator training, adjust current and voltage according to the type of electrode used, and ensure proper surface preparation before welding. This study is expected to serve as a reference for industry practitioners in improving the quality of carbon steel weld joints